Funerary practices in England and Wales - Rugg, Julie, 1964-; Parsons, Brian, active 2018 (Emerald Publishing Limited, 2018)
The Funerary International series comprises essential reference texts for policy-makers, practitioners and academics with an interest in funerary practices globally. Each book has a country or region specific focus, addressing a standard framework of questions to aid comparison. This book sets English and Welsh funerary practice in its wider legal, national and local governance framework, including the continuing role of the Church of England. It provides the historical context for current practice, provides data on new trends in burial and cremation and examines recent developments including direct cremation and alkaline hydrolysis. It provides detail of current practice and includes a detailed description of a typical funeral, including commemorative practice, and discussion of funeral costs. Chapters address the legalities and technicalities of burial and cremation, explaining the concept of burial rights and the technicalities of grave construction, and outlining cremation certification requirements and the process of cremation. This book is a valuable desk-top resource to give a broader frame of reference for policy makers, and to provide explanation of key concepts for practitioners who may be new to this area of work. The text will be of particular value to academics that may be unfamiliar with the legal, technical and professional aspects of the funerary industry. The text is fully referenced, with an additional bibliography of further reading, and includes illustrations, charts, tables, diagrams and boxed text including key information.
Keywords: Funeral rites and ceremonies -- England.; Funeral rites and ceremonies -- Wales.; Social Science, Death & Dying.; Sociology: death & dying.; elektronické knihy; electronic books